Gas Chromatographic Analysis Using Grafted Chromosorb G by Thionyl Chloride And Grignard Reagent - Aziz Ramadan, Abdul; Antakli, Saad; Zahlani, Riad (Asian Journal of Chemistry, 2010)
The surface of a chromosorb G (NAW) support (45-60 mesh, S = 0.5 m2/g) was grafted by two steps, the first one was chlorination of the silica surface using thionyl chloride (SOCl2) and the second by reacting Grignard reagent with chlorophenyl magnesium. A hybrid surface structure (organic/inorganic) of the chromosorb had an extra characteristics of hydrophobicity. The variation of surface grafted support was realized by plotting the relationship between variation of the logarithm of retention volume Vs and the reverse of absolute temperature log Vs = f(1/T). Distinguish the new support with a good stability at high temperature degrees which enable its application in gas chromatography. Essential oils' mixtures (α-pinene, β-pinene, cineole, fenchone, borneol and anethole) and some fatty acid (C8, C10, C12, C14 and C16) in standard (GLC-30) and in laurel oil extracted from wild fruit and cultivated laurius nobilis were determined using the modified chromosorb G by gas chromatographic analysis. The analytical results were characterized by high preci-sion, accuracy and reproducibility.